EFEKTIVITAS PIJAT OKSITOSIN TERHADAP PRODUKSI ASI PADA IBU MENYUSUI DI BIDAN PRAKTIK MANDIRI (BPM) ERNITA KOTA PEKANBARU - Hirza Rahmita; Rizka Mardiya (Jurnal Ilmu Kebidanan, 2022)
One of the reasons mothers do not breastfeed is a lack of confidence in her breastmilk production. Oxytocin hormone is an important trigger of prolactin secretion, which plays a role in the milk ejection process/milk ejection reflex. One of the non-pharmacological therapies to activate the oxytocin hormone is back massage or oxytocin massage for nursing mothers. The purpose of this study was to determine the effectiveness of oxytocin massage on milk production in nursing mothers. This type of research is quantitative with a quasi experimental research design. The research was conducted in BPM Ernita, Pekanbaru city. The population in this study were all mothers giving birth in BPM Ernita last 3 months a total of 30 breastfeeding mothers. Sample size of this study was 15 respondents who were given oxytocin massage treatment and 15 respondents as the control group. Data analysis was performed by univariate and bivariate computerization using the Mann Whitney test. The results of this study there was an effectiveness of oxytocin massage. on milk production in breastfeeding mothers at BPM Ernita, Pekanbaru city (p = 0.000). It is hoped that health workers, especially midwives, can apply oxytocin massage and provide additional information about oxytocin massage to increase breast milk production for breastfeeding mothers and their families.